2007
DOI: 10.1007/s10554-007-9270-4
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous pulmonary venoatrial junction: a new perspective

Abstract: The ambiguous PVAJ with its gradual transition from the left atrium to the pulmonary veins defies precise definition even though it plays an important role in the management of atrial fibrillation. Physicians should be aware of variability in the language used to describe the PVAJ and resultant discrepancy in reported anatomical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…The most common abnormality reported so far is the confluent left PVs, which have been reported to be present in 3-29% of the cases who underwent 3-D imagings. [7][8][9][10][11][12][13][14] In a report by Kato et al, 8 a short common left trunk, in which the junction of the lower wall of the LSPV and upper wall of the LIPV lies outside the LA rim, could be seen in 22% (12 of 55 cases), while a long common left trunk was also present in 7% (4 of 55). In this study, we found that 1.5% of cases who underwent PVI of AF have another type of anomalous PV drainage with a conjunction of contralateral inferior PVs.…”
Section: Discussionmentioning
confidence: 93%
“…The most common abnormality reported so far is the confluent left PVs, which have been reported to be present in 3-29% of the cases who underwent 3-D imagings. [7][8][9][10][11][12][13][14] In a report by Kato et al, 8 a short common left trunk, in which the junction of the lower wall of the LSPV and upper wall of the LIPV lies outside the LA rim, could be seen in 22% (12 of 55 cases), while a long common left trunk was also present in 7% (4 of 55). In this study, we found that 1.5% of cases who underwent PVI of AF have another type of anomalous PV drainage with a conjunction of contralateral inferior PVs.…”
Section: Discussionmentioning
confidence: 93%
“…The venoatrial junctions of the pulmonary and other thoracic veins are highly complex structures. 13,15,16 Syncytial atrial myocardium extends into the veins; however, the orientation of the fibers typically changes around the venoatrial junction providing a sphincter-like action during atrial contraction, limiting pulmonary venous regurgitation. This transition in fiber orientation, however, is gradual, and no distinct anatomic landmark (valves, ridge, etc.)…”
Section: Relevant Anatomymentioning
confidence: 99%
“…Four discrete pulmonary venous (PV) ostia are not always present and may represent a minority of anatomies 12 . PV variants including a common left trunk and accessory PVs, particularly associated with the right pulmonary vein (RPV) complex are observed in up to 44% of patients 13 . Little data exist regarding the impact of such variants on ablation outcomes.…”
Section: Editorial Commentmentioning
confidence: 99%